Analysis of Consumer Purchasing Decisions through Product Quality and Promotion on Pam Pam Fried Chicken Products in the District of Pamulang, South Tangerang City - Udin Ahidin (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
This study is to determine the effect of product quality partially on consumer purchasing decisions on Pam Pam Fried Chicken in Pamulang Subdistrict Area, to determine the effect of partial promotion on consumer purchasing decisions on Pam Pam Fried Chicken in Pamulang Subdistrict Area, to determine the effect of product quality and promotion together with consumer purchasing decisions on Pam Pam Fried Chicken in the Pamulang District Area, and to find out the company's efforts to improve consumer purchasing decisions on Pam Pam Fried Chicken in the Pamulang District Region .Quantitative associative research methods with a verification approach. The population in this study Pam-Pam Fried Chicken consumers amounted to 7,108 consumers in the District of Pamulang, while the sample taken was 100 respondents using the slovin formula, then a proportional random sampling was done because the research object contained 4 (four) branches. Collecting observational data, questionnaires and literature studies. The data analysis method uses validity test, reliability test, classic assumption test, simple linear regression test, multiple linear regression test, correlation coefficient test (product moment), determination coefficient test, hypothesis test (t-test and f-test) . The results showed that there was a positive and significant effect between product quality partially on purchasing decisions. It can be seen from the simple linear regression coefficient of 0.65. The coefficient of determination is 0.6%, t count 2.719> t table 1.984. There is a positive and significant influence between promotion partially on purchasing decisions. It can be seen from the simple linear regression coefficient of 0.32. The coefficient value of determination is 0.2, t count 2.112> t table 1.984.